(untitled) (Global Journal of Human-Social Science, 2021)
The research is aimed at finding out whether the multiple-choice mathematic items of Ondo State Joint Senior Secondary II Promotion Examination OSJSSPE administered in 2015 function differentially in terms of the gender male and female of the examinees and also investigate the general performance of students in the OSJSSPE multiple choice mathematics items administered in 2015 The study employed an ex-post facto research design A sample of 3 135 examinees was selected from a population of 52 922 examinees who sat for the examination using two-stage random sampling techniques One research question was raised and one hypothesis formulated and tested for significance at p 0 05 level The analyses revealed that the general performance of the students in the OSJSSPE multiple choice mathematics items administered in 2015 was high However the examinees of equal ability from both male and female students had a different probability of answering some items correctly thus the multiple-choice mathematics items of OSJSSPE administered in 2015 functioned differentially on male and female examinees